Changes in kidney functions following acute infusion of low molecular weight polyvinylpyrrolidone in male rats - Qi Yan; Qingshang Yan; Henry Shen; Tong Wang (Physiological Reports)
Abstract Polyvinylpyrrolidone (PVP), a water‐soluble homopolymer, has been widely used in food, beverage, medical, and experimental tissue preparations. However, the effect of PVP on renal functions remains unknown. We investigated the acute administration of low MW of PVP on renal functions and whether it produces a toxic effect on the kidney. Renal clearance experiments were performed in rats and showed PVP infusion elicited significant diuretic and natriuretic effects. Urine volume, absolute (ENa), and fractional (FENa) Na+ excretion were significantly increased. A relatively small kaliuretic effect was also observed. After 2 h of PVP infusion, blood urea nitrogen (BUN) and urinary concentrations of beta‐N‐glucosaminidase (NAG) did not change significantly. Alpha‐1‐microglobulin, an indicator of proximal tubule absorption ability, excretion increased 12‐fold, indicating that a large portion of the fluid and Na+ loss is due to reduced absorption in the proximal tubule. The 24‐fold increase in ENa and the 12‐fold increase in α1‐microglobulin excretion suggest that fluid and electrolyte absorption were also reduced in other nephron segments. We conclude that acute low molecular weight PVP infusion produces diuretic and natriuretic effects due to the osmotically induced reduction of proximal tubular absorption, and acute PVP infusion does not cause renal damage.